Recent update of 3D printing technology in pharmaceutical formulation development - Gaurav; Hasan N.; Malik A.K.; Singh V.; Raza K.; Ahmad F.J.; Kesharwani P.; Jain G.K. (My University, 2025)
In modern world, Pharma sector observes steep increase in demand of personalized medicine. Various unique ideas and technology were proposed and implemented by different researchers to prepare personalized medicine and devices. 3-dimensional printing (3DP) is one of the revolutionary technologies which can be used to prepare tailored medicine via CAD (Computer Aided Design) software. 3DP allows researchers to manufacture customized dosage form with desired modifications in geometry which would in turn alter dosage behaviour of the product with reduced side effects. Current achievement of 3DP includes personalized and adjustable dosage form, multifunction drug delivery systems, medical devices, phantoms, and implants specific to patient anatomy. Additionally, 3DP is employed for preparing tailored regenerative medicines. This review focuses on 3DP use in pharmaceuticals including drug delivery systems and medical devices with their method of fabrication. Additionally, different clinical trials as well as different patents done till date are cited in the paper. Furthermore, regulatory issues and future perspective related to 3 D printing is also well discussed. © 2021 Informa UK Limited, trading as Taylor & Francis Group.